Stabilization of cyclic water tetramers and dimers in the crystal host of 2D coordination networks: electrical conductivity and dielectric studies. (9th September 2020) - Dutta, Basudeb; Ghosh, Sourav Ranjan; Ray, Apurba; Jana, Srikanta; Sinha, Chittaranjan; Das, Sachindranath; Jana, Atish Dipankar; Mir, Mohammad Hedayetullah
Abstract : Construction of Zn(ii )-based 2D coordination polymers for selective recognition of water tetramers and dimers in crystal hosts and their exploitation in electrical studies. Abstract : Water plays a pivotal role in many biological and chemical processes in a living body. Therefore, it is a challenging task to predict a suitable host for confinement of aqua molecules. Here, two new isostructural two-dimensional coordination polymers (2D CPs) {[Zn(fum)(4-nvp)2 ]·2H2 O} n (1 ) and {[Zn(mes)(4-nvp)2 ]·H2 O} n (2 ) (H2 fum = fumaric acid and 4-nvp = 4-(1-naphthylvinyl)pyridine and H2 mes = mesaconic acid) have been synthesized and structurally characterized by single crystal X-ray crystallography (SCXRD). The SCXRD reveals the presence of carboxylate bound cyclic water tetramers and water dimers in compounds 1 and 2 respectively, within rectangular grids of 2D coordination layers. Binding energies of the cavity bound tetramer as well as the dimer have been estimated computationally. The PXRD study of both the compounds shows reversible water desorption and re-absorption upon heating and cooling. The π⋯π and C–H⋯π interactions among the axially bound 4-nvp ligands are responsible for interdigitation of successive 2D coordination layers into a 3D supramolecular architecture. In addition, the impedance study shows that compounds 1 and 2 exhibit interesting temperature dependent dielectric properties.